Asthma, social isolation and loneliness, and risk of incident osteoarthritis - Ziyi Wu; Xukun Luo; Pengcheng Dou; Tang Liu; Jian Zhou (Arthritis Research & Therapy)
Abstract Background Incidence of osteoarthritis (OA) was increased in patients with asthma, while no prospective cohort study has tested the association of asthma with OA, and the modified effect of social isolation and loneliness remains unclear. Methods This prospective cohort study included 448,920 participants without OA at baseline from UK Biobank cohort. The evaluation of asthma was based on diagnosis and self-reported history. The outcome was OA including knee OA, hip OA and hand OA by referring to hospital admission records. Two Cox regression models were constructed to assess the relationship of asthma and risk of OA. Results With a median of 12.5 years of follow up, a total of 57,573 incident OA were recorded. Compared with participants without asthma, the hazard ratios (HRs) were 1.32 (95% CI: 1.29–1.35) for all OA, 1.21 (95% CI: 1.16–1.25) for knee OA, 1.12 (95% CI: 1.07–1.18) for hip OA and 1.62 (95% CI:1.42–1.85) for hand OA in participants with asthma. In addition, we found that social isolation and loneliness significantly modified the associations of asthma with OA (P-interaction < 0.001). Asthma was a stronger predictor of OA than lifestyle risk factors including smoking, alcohol and healthy diet. Conclusions In this cohort study of UK Biobank participants, asthma was related to increased risk of OA; such association was more pronounced among those with higher social isolation or loneliness score.